(untitled) (Cadernos de Sociomuseologia, 2014)
This paper summarizes part of the research developed under the Doctoral Thesis in Museology. It focuses on the ’case study’ of a local root museum process: Museu – Biblioteca Condes de Castro Guimarães, the sole institution museum in Cascais for half a century. Based on the epistemological field on Socio-museology research, upon primary sources, secondary and complementary bibliography, we tried to comprehend how the main founders of this institution thought, perceived and established the museological function at its origins. The research was developed in two complementary orientations: on one hand we studied the thoughts and actions of the museum curator João Couto through the content analysis methodology of their scholarly previously published texts. In parallel, we studied the history of the museum starting from the 1930s until the 1940s. This allowed us to perceive that, very early, the social and educational functions were present and continued to be developed over the decades that followed. We demonstrate the relevance of the curator’s work in the the construction of a cultural institution, engaging in social, cultural, and educational pioneering practices to benefit the community, and that we believe influenced the work of Museu Nacional de Arte Antiga, in Lisbon. Key-words: Museology; Socio-museology; Education; Local Museums; Community.